Uniform Domain Name Dispute Resolution Policy: What Is It? - Rusli, Hardijan (LAW REVIEW, 2003)
Internet domain names raise some unique trademark issue. One of the important issue is  the interface between domain names and trademarks. A mark comprised of an internet  domain name that does not function as an identifier of the source of goods or service  cannot be regarded as a trademark or service mark. Domain names principally are not the same thing as marks and are used for many purposes other than the identification of a producer or seller of goods or services. Domain names function is mainly as connection  facilitation between computers through the Internet but now it seems that there is another function of domain names, because of their easy-to-remember and human friendly form, domain names have become to constitute business or personal identifiers (First WIPO Internet Domain Name Process: Archive, http://wipo2.wipo.int/processl/, 3/17/03). Businesses have come to realize the significant potential of an internet web site as a means for providing information and offering goods or services directly to the consumer public. The domain name, because of its purpose of being easy to remember dan to identify, often carries an additional significance which is connected with the name or mark of a business or its product or sevices. Domain names as business or enterprise  identifiers have come into conflict with trademarks. The potential for conflict inherent  in the two different systems of registration has been exploited by persons who have made it a practice to register the trademarks of other persons or enterprises as domain names for themselves ("cybersquatting") like Mustika Ratu case in Indonesia. The Mustika Ratu dispute was trialedat District Court of Central Jakarta. Edmon akarimfrom Legal Research Center in Technology Law of Law Faculty, University of Indonesia andAgung Damarsasongko.from Directorate General ofHAKI (Intelectual Property Right) as expert witnesses in the case gave explanations that to register a trademark as a domain name is not a trademark infringe, because domain name is used for information and trademark is used for industry benefit.  (http://www,juducial-news.com/News,assp?Pindex=505), A significant number of disputes apparently never rise to the level of being reported. A large proportion may remain unresolved, or may be resolved informally pursuant to a settlement between the parties. Intellectual property right owners have made it clear throughout the WIPO Process that they are incurring significant expenditures to protect and enforce their rights in relation to domain names. Existing mechanisms for resolving conflicts between trademark owners and domain name holders, before 3 January 2000, were often viewed as expensive, cumbersome and ineffective. Recommendations of the International Ad Hoc Committee (IAHC), organized at initiative of the Internet Societys (ISOC) and the Internet Assigned Numbers Authority (1ANA), took note of the tension that existed between domain names and intellectual property rights and included specific procedures designed to resolve conflicts between the two. Uniform Domain Name Dispute Resolution Policy (UDRP) which has been adopted, on 26 August 1999, by the Internet Corporation for Assigned Names and Numbers (ICANN) is incorporated by reference into the Registration Agreement and sets forth the terms and conditions in conection with a dispute between the domain name holder and any party other than the registrar over registration and use of an internet domain name registered. The Uniform Domain Name Dispute Resolution Policy (UDRP) began ramp up implementation on 1 December 1999 and became fully operational on 3 January 2000. ICANN is a new organization formed to manage the policy and technical aspects of the Internet Domain Name System.  Although the policy provides that most domain-name disputes will be resolved by the  courts, it also calls for administrative dispute-resolution proceedings to enable streamlined, economical resolution of disputes arising from alleged "abusive registration."  This writing explains how the Mandatory Administrative Procedure Concerning Abusive  Registrations of UDRP works because lawyers in Indonesia should know it.